Implementasi Zahir Accounting Versi 6 Pada Toko Besi Surya Jaya Bogor - Aryanto, Ayu Lestari; Wasiyanti, Sri; Miharja, Kasmanto (LPPM Universitas Bina Sarana Informatika, 2023)
In a company, financial reports have a very important role in order to reach the quality of the company, to find out whether the financial position has increased or decreased. Financial reports are also a tool for processing company data related to accounting. This research uses a direct observation method (observation) by directly observing financial transaction management activities carried out using cash records which are then recapitulated manually, an interview method to obtain some information regarding existing problems in the company, a literature study method to strengthen the research author. Surya Jaya Bogor Iron Shop is engaged in selling various building materials. Currently, companies already carry out accounting records manually, namely by writing and using Microsoft Excel, but manual recording is still not able to speed up company performance and there are still many obstacles that cause accounting records to disappear at any time. Therefore, this research focuses on processing accounting data at the Surya Jaya Bogor Iron Shop using the Zahir Accounting Version 6 Build 13 application which is easy to use and understand so that it can form financial reports quickly and produce financial reports in accordance with financial accounting standards.